1999
DOI: 10.1093/ajcp/112.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Receptor Contents in ThinPrep-Processed Fine-Needle Aspirates of Breast

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 5 publications
0
38
0
1
Order By: Relevance
“…11,26 In contrast, other reports showed that microwave-stimulated epitope retrieval can be applied successfully on smears fixed in alcohol, formalin, or processed by ThinPrep. 15,16,27,28 The low ER immunoreactivity in our initial smears, however, prompted us to try heat-induced epitope retrieval on all negatively staining smears that had been fixed in 10% formalin, followed by repeat ER staining. A negative-to-positive conversion was observed in 18 of 20 smears with an increased nuclear staining intensity.…”
Section: Discussionmentioning
confidence: 99%
“…11,26 In contrast, other reports showed that microwave-stimulated epitope retrieval can be applied successfully on smears fixed in alcohol, formalin, or processed by ThinPrep. 15,16,27,28 The low ER immunoreactivity in our initial smears, however, prompted us to try heat-induced epitope retrieval on all negatively staining smears that had been fixed in 10% formalin, followed by repeat ER staining. A negative-to-positive conversion was observed in 18 of 20 smears with an increased nuclear staining intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that the diagnostic accuracy of ThinPrep-processed breast FNA biopsy specimens is as good as conventionally prepared specimens. ThinPrep processing has the added benefits of allowing flow cytometry 42 and immunohistochemistry, 43 -44 including estrogen and progesterone receptors, 45 to be performed. ThinPrep also has been extremely well accepted by clinicians because of the ease of specimen preparation, and it has remained the method of choice at our institution for the processing of breast FNAs…”
Section: Discussionmentioning
confidence: 99%
“…Excellent results can also be achieved using the LBC method. Using TP slides from malignant breast aspirates, Leung and Bėdard [31] reported an overall accuracy of 97 and 89% for the detection of ER and PR, respectively. In another study, stronger immunostaining was observed on TP slides in comparison to histological samples [17].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…Although not statistically significant, a higher number of cases positive for ER and PR was detected on slides prepared by the TP technique in comparison to CS [32]. Microwave antigen retrieval pretreatment before immunostaining is usually advocated for TP slides [31,32]. In fact, a recent multinational study demonstrated a great variability in the detection of ER and PR in breast FNA specimens because of the different types of cytological preparations and the diverse methods of fixation and immunostaining protocols used by the laboratory participants.…”
Section: Ancillary Techniquesmentioning
confidence: 99%